2017
DOI: 10.3748/wjg.v23.i13.2330
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling mediated by TGF-β/Smad pathway in concanavalin A-induced liver fibrosis in rats

Abstract: AIMTo explore the exact interaction between Notch and transforming growth factor (TGF)-β signaling in liver fibrosis.METHODSWe established a rat model of liver fibrosis induced by concanavalin A. Peripheral blood mononuclear cells (PBMCs) were isolated from the modeled rats, and cultured with γ-secretase inhibitor DAPT and TGF-β inhibitor for 24 h. The mRNA levels of Notch and TGF-β signaling were detected by quantitative real-time polymerase chain reaction. Expression of Notch and TGF-β proteins was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…The Notch receptor must be hydrolyzed and cleaved by the protease γ-secretase to release the intracellular domain, thereby activating the signaling pathway. 4,6-diamidino-2-phenylindoleindole (DAPT), as a blocker of the Notch signaling pathway, can specifically block the action of γ-secretase, thereby preventing the activation of Notch [73].…”
Section: Regulation Of the Effect Of Notch Signaling Pathway On Thementioning
confidence: 99%
“…The Notch receptor must be hydrolyzed and cleaved by the protease γ-secretase to release the intracellular domain, thereby activating the signaling pathway. 4,6-diamidino-2-phenylindoleindole (DAPT), as a blocker of the Notch signaling pathway, can specifically block the action of γ-secretase, thereby preventing the activation of Notch [73].…”
Section: Regulation Of the Effect Of Notch Signaling Pathway On Thementioning
confidence: 99%
“…Half of the cranial nerve genes identified were also functionally annotated as participating in or being responsive to TGF beta/BMP signaling (Fig. 3C), including Gdf6; Hes1, a key Notch signaling gene down-regulated by TGF beta inhibitors; and Phox2b, which encodes a TGF beta-regulated transcription factor that acts as a "switch" between sensory and visceral neuron identities and influences their physical position within cranial sensory pathways (D'Autreaux et al 2011;Dias et al 2014;Wang et al 2017).…”
Section: Convergent Coevolution In Cis-regulators Of Craniofacial Nermentioning
confidence: 99%
“…It is broadly accepted that TGF-β1 canonical signaling, also known as the TGF-β1/SMADs signaling pathway, is crucial for the occurrence and progression of hepatic fibrosis, whereas non-canonical signaling, which is associated with multiple different pathways, such as MaPK, Pi3K-aKT and Wnt, also contributes to the activation of HScs and liver fibrosis (7,8). Several previous studies have revealed the existence of crosstalk between Notch and TGF-β signaling in the activation of HScs, and the notch downstream TF HES1 plays an important role in this crosstalk (9)(10)(11)(12)(13). Thus, blocking the signal transduction of TGF-β1 or regulating the effect of SMads on the expression of target genes in order to decrease ecM synthesis and increase ecM degradation may be a promising approach to reversing hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the role of Notch signaling in hepatic fibrosis and the crosstalk between notch and TGF-β signaling. There is evidence that the expression of major components of the notch signaling pathway, including notch3, Jagged1 and the downstream transcription factor (TF) Hairy and enhancer of Split 1 (HeS1), is induced by TGF-β canonical signaling via SMADs (9,10). another study reported that notch signaling also contributes Class C1 decoy oligodeoxynucleotide inhibits profibrotic genes expression in rat hepatic stellate cells to TGF-β-induced expression of a-SMa and coli and, when inhibited, a-SMA and COLI expression decreased (11).…”
Section: Introductionmentioning
confidence: 99%